Pemberdayaan UMKM Kerupuk Kemplang Palembang melalui Digital Entrepreneurship - Tarigan, Eka Dewi Setia; Lores, Linda; Masut, Masut (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to increase the capacity and competitiveness of the Pak Hamdani Kemplang Crackers MSME in Deli Serdang Regency through the application of digital entrepreneurship concepts. The main challenge faced by business owners is limited knowledge and skills in utilizing digital media for product marketing. The activity was implemented through a participatory approach, including training, mentoring, and hands-on practice. Over the two days of the activity, participants received training on creating digital business accounts, social media management, promotional content strategies, and simple product photography techniques. The results of the activity showed an 80% increase in participant understanding based on pre- and post-test results. Partners were also able to create digital business accounts and upload promotional content independently. This program is expected to increase sales and expand the market reach of local Palembang products, as well as serve as a model for digital-based empowerment for other MSMEs in the surrounding area.